2013
DOI: 10.1556/aagr.61.2013.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Agro-morphological diversity and stability of durum wheat lines (Triticum durum Desf.) in Algeria

Abstract: This study focuses on the genetic potential and genotypic stability of 17 durum wheat genotypes during three crop years under wet conditions in the north of Algeria (Algiers). The results showed highly significant (P<0.001) agro-morphological diversity between the genotypes and a genotype × environment interaction for all the traits except for fertile spikelet number. Wricke's ecovalance (w i ), Shukla's stability variance (σ i 2 ), heterogeneity variance (%HV) and the incomplete correlation (%IC) method were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…To this end, two pedigree lines (G1 and G4) selected in Algeria and three commercialized varieties (G9, G10 and G11) were tested in the field. These lines are composed of F15 seeds resulting from simple crosses between 4 parental varieties: Saadi, Siméto, Ardente and Waha (Mekliche et al, 2013). The main characteristics of these genotypes are shown in Table 1.…”
Section: Vegetal Materialsmentioning
confidence: 99%
“…To this end, two pedigree lines (G1 and G4) selected in Algeria and three commercialized varieties (G9, G10 and G11) were tested in the field. These lines are composed of F15 seeds resulting from simple crosses between 4 parental varieties: Saadi, Siméto, Ardente and Waha (Mekliche et al, 2013). The main characteristics of these genotypes are shown in Table 1.…”
Section: Vegetal Materialsmentioning
confidence: 99%
“…Assessment of genetic diversity due to discovering new alleles or genes in the natural populations and old varieties maximize the efficiency of breeding programs and also offers new scenarios in order to discover the key genes and improves varieties with desirable traits (POUR-ABOUGHADAREH et al, 2017b). Investigation of genetic diversity in durum wheat has a long history and up to now numerous studies reported the high level of agro-morphological and molecular variability among this germplasm (TESFAYE et al, 1991;AUTRIQUE et al, 1996;SOLEIMANI et al, 2002;MEDINI et al, 2005;MEKLICHE et al, 2013;POUR-SIAHBIDI et al, 2013;ETMINAN et al, 2016;BALOCH et al, 2017;ETMINAN et al, 2017;ETMINAN et al, 2019). Of these, molecular markers are key tools to study the genetic diversity and analysis of population structure.…”
Section: Introductionmentioning
confidence: 99%